PENGKAYAAN Artemia sp DALAM LARVIKULTUR IKAN KOMET (Carassius auratus) - Muliani Muliani; Eva Ayuzar; M Rizal (Berkala Perikanan Terubuk, 2016)
This study aimed to determine the effect of Artemiasp enrichment with vitamin and selco emulsionson the growth and survivalrate of goldfishlarval(Carassiusauratus). This research conducted experiments with a Completely Randomized Design (CRD).Hatched Artemianauplii that had been enriched with vitamin and selco emulsions for 2 hours of treatment A (enrichment artemianauplii with vitamins dose of 0,25 ml/L), treatment B (enrichment artemianauplii with selco emulsions dose of 0,25 ml/L), treatment C (enrichment artemianauplii with vitamins and selco emulsions each dose of 0,125 ml/L) and treatment D (without enrichment as control). The results showed that Artemia enrichment with vitamin and selco emulsionsgave significant result (P < 0.05) on the growth and survival of larvae goldfish. Where the best results obtained at the treatment B with survival (36,6 %), absolute growth in length (6,49 mm) and daily specific grothw rate (13,53 %). So it can be concluded that the best treatment for the growth and survival is on Artemia enrichment with selco emulsions dose of 0.25 ml/L.